PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM (STUDI SUB SEKTOR MAKANAN DAN MINUMAN TERDAFTAR DI BEI TAHUN 2016-2020) - Dita Marisa Putri; Syaiful Sahri (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
This research was carried out on sub-sector companies of the Indonesian Food and Beverage Registered in 2016 - 2020. This research attempted to find out (1) The effect of Debt on Equity Ratio on Stock Prices (2) the effect of Return On Assets on Stock Prices ( 3) the effect of earning Per Share on Stock Prices and (4) the effect of Debt To Equity Ratio, Return On Asset, simultaneously Earning Per Share on Stock Prices.The research method Used in this research was Quantitative Approaches. The sampling technique used in this research was determined by purposive sampling methods with 10 Company Samples. The data analysis method in this research was multiple regression analysis and classical assumption test consisting of normality test, multicolouriarity test, heteroscedacity test, autocorrelation test, t test, f test and determination coefficient test.The research findings revealed that (1) Debt To Equity Ratio (DER) had negative and significant effects on stock prices, (2) ROA had no siginificant affect on Stock Prices, (3) EPS had positive and significant effect on stock prices. DER, ROA, EPS simultaneously affected the stock price. The determination coefficient test results obtained R2 of 0.896 Or 89.6% which means that the variable ability of Debt To Equity, Return On Assets And Earning Per Share in explaining variables of the stock price was 89.6% while the remaining 10.4% was explained by other factors that were not included in research.Keywords: Debt to equity ratio, return to asset, earning per share, stock price